Establishing a new human pneumococcal standard reference serum, MPRSS-01 - Joseph M. Antonello; Rocio D. Murphy; Chitrananda Abeygunawardana; Juliana C. Malinverni; Rajam Gowrisankar; Tina Green; Rebecca Greway; Jenna Schmauch; Adrienne Howlett; Cyrille J. Bonhomme; Katrina M. Nolan (mSphere)
ABSTRACT Measuring the immunogenicity of pneumococcal vaccines involves the use of immunoassays to measure serotype-specific immunoglobulin G (IgG) antibody levels post-vaccination with the current Streptococcus pneumoniae human reference serum standard (007sp) for anti-pneumococcal capsule antibodies. Development of new pneumococcal conjugate vaccines (PCVs) with additional serotypes not in 007sp (e.g., V116, a 21-valent PCV) requires a new reference serum. Antibody concentrations to 33 pneumococcal serotypes were assigned in a new Merck Pneumococcal Reference Serum Standard (MPRSS-01; Merck Pneumococcal Reference Serum Standard) using the pneumococcal electrochemiluminescence assay. MPRSS-01 was generated by pooling high-titer serum samples from adults immunized with either 23-valent pneumococcal polysaccharide vaccine (PPSV23) or V116. For the 24 serotypes with established IgG concentrations, the corresponding antibody concentrations in MPRSS-01 were assigned via direct calibration to 007sp, while a cross-standardization approach was used for the nine novel serotypes. Serotype 7F was initially chosen as the reference calibrator for cross-standardization due to parallelism across dilution–response curves demonstrated across all 33 serotypes, and an evaluation of the single-calibrator approach was conducted for the 24 serotypes. Potential systematic bias from using a unique serotype for calibration was identified and addressed by further adjusting the estimated IgG concentrations of the nine novel serotypes. Using the final MPRSS-01 antibody concentration assignments, and the calibration factor relating MPRSS-01 to 007sp, antibody concentration assignments for 007sp were provided for the nine novel serotypes. This proposal was accepted by the Center for Biologics Evaluation and Research (CBER), enabling V116 to bridge old and new human pneumococcal reference sera.IMPORTANCEImmunogenicity of pneumococcal vaccines is measured using post-vaccination serotype-specific immunoglobulin G (IgG) antibodies in serum using enzyme-linked immunoassays with the 007sp reference serum containing serotype-specific IgG for 24 pneumococcal serotypes. With the development of next-generation PCVs, a new S. pneumoniae reference serum standard was needed to include serotypes beyond the existing 24 in 007sp. In this study, antibody concentrations to 33 pneumococcal serotypes were assigned in a new Merck Pneumococcal Reference Serum Standard (MPRSS-01) using the pneumococcal electrochemiluminescence assay, enabling V116 to maintain the link to the historical human pneumococcal standard reference serum while utilizing the new human pneumococcal reference serum.